1995
DOI: 10.1128/jcm.33.7.1784-1786.1995
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria meningitidis with decreased susceptibility to penicillin in Saskatchewan, Canada

Abstract: Moderately penicillin-resistant Neisseria meningitidis is rare in North America. We report an outbreak of meningococcal disease in Saskatoon, Saskatchewan, Canada, with serogroup C N. meningitidis. The MICs of penicillin ranged from 0.12 to 0.25 g/ml, and all isolates showing decreased susceptibility had identical genomic fingerprints when they were compared by pulsed-field gel electrophoresis. Our data indicate that N. meningitidis that is moderately resistant to penicillin is prevalent in Saskatchewan, Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There seems to be an increasing number of reports of N. meningitidis strains with a reduced susceptibility to penicillin G in Canada (6,14,26). In the present study, 13 such strains were found, none of which produced beta-lactamase with the nitrocefin disk.…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be an increasing number of reports of N. meningitidis strains with a reduced susceptibility to penicillin G in Canada (6,14,26). In the present study, 13 such strains were found, none of which produced beta-lactamase with the nitrocefin disk.…”
Section: Discussionmentioning
confidence: 99%
“…In Belgium, serogroup B is the predominant sero‐group causing meningococcal disease, followed by serogroup C. No effective vaccine is currently available for protection against group B meningococcal disease, because the B capsular polysaccharide is not immunogenic in humans [4]. The recent emergence of penicillin‐resistant meningococcal strains [5,6] may create additional therapeutic problems.…”
Section: Distribution Of Serotypes and Subtypes Among 568 Serogroup Bmentioning
confidence: 99%